2012
DOI: 10.1111/j.1542-4758.2012.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Uremic pleuritis in chronic hemodialysis patients

Abstract: Chronic hemodialysis (HD) patients are predisposed to several complications associated with pleural effusion. In addition, uremia can directly cause pleuritis. However, there are inadequate data about pathogenesis and natural course of uremic pleuritis. In this study, 76 chronic HD patients with pleural effusion admitted to the Respiratory Center of Masih Daneshvari Hospital, in Tehran, Iran between June 2005 and May 2011 were evaluated to figure out the etiology of their pleural disease. Among these patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 13 publications
2
21
0
2
Order By: Relevance
“…The fluid overload between HD sessions and abnormal permeability of the pulmonary microcirculation have been cited as causes of acute pulmonary edema (noncardiogenic) and pleural effusion (28) that can reduce volumes and lung capacity over time. This respiratory complication changes the ventilation/perfusion relationship (with or without the presence of anemia), reduces gas exchange, tissue oxygenation, and, consequently, functional capacity (activities of daily living) and exercise tolerance (29)(30)(31) .…”
Section: Discussionmentioning
confidence: 99%
“…The fluid overload between HD sessions and abnormal permeability of the pulmonary microcirculation have been cited as causes of acute pulmonary edema (noncardiogenic) and pleural effusion (28) that can reduce volumes and lung capacity over time. This respiratory complication changes the ventilation/perfusion relationship (with or without the presence of anemia), reduces gas exchange, tissue oxygenation, and, consequently, functional capacity (activities of daily living) and exercise tolerance (29)(30)(31) .…”
Section: Discussionmentioning
confidence: 99%
“…Uremic pleuritis is a unique etiology for HD patients. Although it is classically thought of as pleural effusion in patients with ESRD without HD, it has recently been reported that uremic pleuritis exists even in patients already receiving HD and is underestimated [2]. A recent study reported that uremic pleuritis comprised 40% of exudative effusion and was the most common etiology of exudative effusion [1].…”
Section: Discussionmentioning
confidence: 99%
“…Common etiologies of pleural effusion in this patient group are heart failure, volume overload, parapneumonic effusion, tuberculotic pleuritis, and uremic pleuritis [2]. Because of the frequency with which this complication is associated with volume overload or heart failure, empirical reduction of the dry weight (DW) is often attempted without thoracentesis [1].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Pleural effusions from pneumonia or uremic pleuritis typically are exudative by both criteria. [7][8][9][10][11][12][13][14][15] In addition, transudative effusions as a result of CHF or CO are paucicellular with low neutrophil counts. Pleural effusions resulting from pneumonia or uremic pleuritis have a higher TNC and ANC and higher protein and LDH concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Cell counts, especially neutrophil counts, are higher in uremic pleural effusions than in CHF. [7][8][9] To our knowledge, the effect of ESRD on the PFA as a result of CO in the absence of clinical signs of uremic pleuritis has not been reported to date. We found a statistically signifi cant difference in protein concentrations and pleural fl uid/serum protein ratios in pleural effusions in ESRDCOCHF compared with SCHF.…”
Section: Esrd With Co or Chfmentioning
confidence: 95%